Meaning in the structure of the Bhāgavata Purāṇa - Mishra, Anand (International journal of Hindu studies, 2018)
This article examines the strategies and methods employed by Vallabhācārya (1479-1531 CE) to establish Bhāgavata Purāṇa as an authoritative source of Vedānta. Following the methodology of grammarians and ritualists, Vallabhācārya analyzes the structure of Bhāgavata Purāṇa and associates its form with semantic concepts, especially the ten-fold divine play (līlā) of God. Further, he correlates this form with the body of God—Śrīnāth-jī. In this manner, he attempts to show the divine nature of Bhāgavata Purāṇa and to prove that it is the highest authoritative text (pramāṇa).